ART AS TRANSPORTER. - Wasilewski, Marek (PAJ: A Journal of Performance & Art, 2004)
Focuses on the group show "Raw" shown from March 1 to April 6, 2003 held at the Smack Mellon gallery in Brooklyn, New York. Offer of the art exhibition of a collection of works on video, computer, drawing, sound, photography and performance arranged by curator Denise Carvalho; Aim of the set to present a sense of chaos and confusion; Observation of the underlying complications of multi-layered irony with the artist's infused spirit.